EFEKTIVITAS KEBIJAKAN SISTEM ZONASI PADA PENERIMAAN PESERTA DIDIK BARU ONLINE DI DINAS PENDIDIKAN DKI JAKARTA - Luksi Dehot, Maria Theovilla; Yasintha, Putu Nomy; Putri Wirantari, I Dewa Ayu (CITIZEN CHARTER, 2021)
DKI Jakarta Provincial Education Office is an agency that implements education policies. One of the educational policies implemented is PPDB online, this policy is implemented with the aim of making it easier for students to register for the desired destination school. The government issued PERMENDIKBUD Number 17 of 2017 which regulates the zoning system on PPDB Online in Jakarta Area. The zoning system is implemented with the aim of leveling education. The purpose of this study is to find out how the effectiveness of the zoning system policy on the acceptance of new online students in Jakarta area . Then the government made a zoning system on PPDB online with the aim of leveling education. The zoning system implemented on PPDB online develops every year with several changes .   Keywords: Effectiveness, PPDB Online, Zoning System, Education Policy